- #1

- 1

- 0

1- let m= m(x;y;z)

solve2((d^3/dx^3)+3(d/dx)(d^2/dy^2)-(d/dx)(d/dy))*m(x;y;z)=0

2-let m=m(x;y;z) solve (ydx+ydz)*m=m

- Thread starter mazen.azhari
- Start date

- #1

- 1

- 0

1- let m= m(x;y;z)

solve2((d^3/dx^3)+3(d/dx)(d^2/dy^2)-(d/dx)(d/dy))*m(x;y;z)=0

2-let m=m(x;y;z) solve (ydx+ydz)*m=m

- #2

- 360

- 1

Oh, solve2? Are you using some software? Which software?

- Last Post

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 0

- Views
- 2K

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 6

- Views
- 3K

- Last Post

- Replies
- 7

- Views
- 10K

- Replies
- 2

- Views
- 2K

- Replies
- 0

- Views
- 2K

- Replies
- 5

- Views
- 9K

- Last Post

- Replies
- 10

- Views
- 10K

- Last Post

- Replies
- 1

- Views
- 2K